The effect of humanitarian logistics service quality to customer loyalty using Kansei engineering: Evidence from Indonesian logistics service providers - Ilyas Masudin; Nika Tampi Safitri; Dian Palupi Restuputri; Rahmad Wisnu Wardana; Ikhlasul Amallynda (Cogent Business & Management, 2020)
This article identifies the effect of logistics service quality on customer satisfaction and customer loyalty with customer trust as a moderating variable from the context of Indonesian humanitarian logistics providers. In this study, the service quality was provided into three variables, namely the quality of personnel services, the quality of operation services, and the quality of technical services. The conceptual model is generated by introducing three other variables, namely, customer satisfaction, loyalty, and trust as a moderating variable. Eighty respondents completed the formal survey. The pilot test and the structured questionnaire were analyzed using the SPSS 21 and Smart-PLS 2.0 to evaluate the relationship between the variables. The results of this study were accepted three out of eight hypotheses. The personnel service quality has a significant impact on customer satisfaction, customer satisfaction has a significant effect on customer loyalty, and technical service quality has a considerable impact on customer loyalty. The use of Kansei engineering for humanitarian logistics service in this study would provide a different perspective in terms of capturing the voice of customers' perception of relief logistics service quality
Keywords: 650; humanitarian logistics; service quality; Kansei engineering